STRATEGI KOMUNIKASI BALI DEAF COMMUNITY DALAM MENSOSIALISASIKAN BISINDO (BAHASA ISYARAT INDONESIA) KEPADA MASYARAKAT - Deviyanti, Ni Putu Laksmitha; Joni, Ida Sugiarica; Alit Suryawati, I Gusti Agung (E-Jurnal Medium, 2018)
ABSTRACT Non-verbal communication such as sign language became the focus in this research, how the deaf can deliver the messages by body language and expression that used in sign language. The purpose of..this research is to know about the communication strategy that used by Bali Deaf Community in socialize BISINDO (Indonesian sign languages) to the public. Data collection is done by participant observation method, interview and documentation study. The type of this research is qualitative research with post-positivist paradigm. The analysis technic that is used in this research is Milles and Huberman analysis and used purposive sampling technic to determine the informant. The result of this research..showed that there are the effective communication strategy in socialize BISINDO (Indonesian sign languages) to the public, those are (1) determine the communicator who is competent to deliver the messages, (2) set the socialization targets, (3) Arrange the message that will delivered to the public by providing sign language module, (4) and social media usage in socialize BISINDO (Indonesian sign language). Keywords: BISINDO (Indonesian sign languages), The Deaf, Communication Strategy